Total liberation : the power and promise of animal rights and the radical earth movement - Pellow, David N., 1969- (University of Minnesota Press, 2014)
This volume is a story about inequality, its many forms and far reaching consequences, and unconventional efforts to challenge it. The book expands our understanding of inequality by making sense of the often tense and violent relationships among humans, ecosystems, and nonhuman animal species. It considers how radical environmental and animal rights movements challenge these socio-ecological inequalities through a vision they call total liberation.